Optimization of the jaloe kayoh seat design using the quality function deployment (QFD) method based on anthropometric measurements of the Acehnese Society - Akram Tamlicha; Samsul Rizal; Iskandar Hasanuddin; M.M. Noor; Rahmad Ferdiansyah; Sri Rahmawati; Nazaruddin Nazaruddin (Politeknik Negeri Lhokseumawe, 2023)
Jaloe Kayoh is a traditional canoe used by Aceh's fishing communities to catch fish in downstream rivers and shallow waters. The current Jaloe Kayoh design does not meet ergonomic aspects, especially in the user's seat position component. It is known from the results of distributing the Nordic Body Map (NBM) questionnaire at the initial stage of the study which was distributed to 30 respondents, that 9 out of 27 fisherman's body parts were in the